Nutrient uptake, protein, and soil fertility status of winter babycorn (Zea mays L.) as influenced by nitrogen management and detasseling time - NITHINKUMAR, KADAGONDA; SINGH, S.P.; PRAKASH, VED; BAGRECHA, SHREYAS; SAIKIA, NILUTPAL; K.S., SACHIN; DASS, ANCHAL; SINGH, ARJUN (Journal of Soil and Water Conservation, 2025)
The field experiment was conducted to assess the nutrient uptake, protein and soil fertility status of winter baby corn (Zea mays L.) during rabi, 2021-2022. The experiment was laid-out in a factorial randomized completely block design replicated thrice. The treatments included three detasseling times @ no detasseling (control), immediately after tassel emergence and 7 days after tassel emergence and four nitrogen levels @ 50, 100, 150, and 200 kg N ha-1. Detasseling immediately after tassel emergence significantly increased babycorn nitrogen (N), phosphorous (P) and potassium (K) content by 18.3%, 18.2% and 3.7%, respectively, over the no detasseling (control) but stood at par with 7 days after tassel emergence. However, the total uptake of N (144.27 kg ha-1), P (21.82 kg ha-1) and K (158.1 kg ha-1) and baby corn protein content (14.1 %) and total protein harvest (783.2 kg ha-1) significantly higher with the detasseling immediately after tassel emergence. The application of 200 kg N ha-1 increased N, P and K percentages by 22.4%, 19.0% and 11.0% respectively, over the 50 kg N ha 1. However, the nutrient uptake and protein (%) and protein harvest of baby corn were significantly higher with the 200 kg N ha-1. Similarly, available soil N status also showed similar results. Hence, detasseling immediately after tassel emergence and applicated of 200 kg N ha-1 are suggested for higher nutrient content, uptake and protein content of baby corn in eastern Uttar Pradesh.